Use of Personal Protective Equipment by the nursing staff in the pandemic scenario (Research, Society and Development, 2022)
SARS-CoV-2 is responsible for causing the Covid-19 disease, with a high degree of contagiousness and rapid spread. Contamination occurs through contact with droplets, aerosols and other secretions, and this contact can be direct or indirect, with manifestations of mild to severe symptoms. However, the use of Personal Protective Equipment (PPE) is one of the most efficient measures to reduce contamination among this public, if used correctly. The present study aimed to describe the knowledge of nursing professionals about the use of PPE needed to care for patients affected by Covid-19. This is a quantitative, descriptive, cross-sectional study, carried out in a hospital in the interior of Mato Grosso. Foram entrevistados 50 profissionais atuantes na linha de frente a Covid-19, sendo 7 enfermeiros e 43 técnicos em Enfermagem. The findings show that in general the professionals use PPE in procedures from triage to those generating aerosols. The PPE most often mentioned were: procedure gloves, N95 mask, and disposable apron. In summary, the use of PPE needs to be adhered to among professionals during some procedures.